Development Of The Capital Market, Money Market, And Foreign Exchange Market In Indonesia: A Sharia Economic Perspective - Irwan Fauzy Ridwan; Oyo Sunaryo Mukhlas; Siah Khosyiah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the development of the capital market, money market, and foreign exchange market in Indonesia from the perspective of Islamic economics. In recent years, financial markets in Indonesia have experienced significant growth, especially in sectors that comply with sharia principles. This study examines how these developments affect the Indonesian economy, as well as the challenges and opportunities that exist in the sharia context. The method used in this research is a qualitative approach with descriptive analysis. Data was collected through literature study from various sources, including journals, reports, and official documents related to the capital market, money market, and foreign exchange market in Indonesia. The research findings show that although the Islamic capital market in Indonesia has grown rapidly, there are still some challenges to be faced, such as the lack of public understanding of Islamic investment and the lack of sharia-compliant instruments. In addition, the Islamic money market also shows great potential, but still needs to be encouraged with more supportive regulations. On the other hand, the foreign exchange market in the sharia context is still relatively new and requires further attention to develop transaction mechanisms that are in accordance with sharia principles